2012
DOI: 10.1158/1055-9965.epi-12-0066
|View full text |Cite
|
Sign up to set email alerts
|

Common Breast Cancer Susceptibility Variants inLSP1andRAD51L1Are Associated with Mammographic Density Measures that Predict Breast Cancer Risk

Abstract: Background Mammographic density adjusted for age and body mass index (BMI) is a heritable marker of breast cancer susceptibility. Little is known about the biological mechanisms underlying the association between mammographic density and breast cancer risk. We examined whether common low-penetrance breast cancer susceptibility variants contribute to inter-individual differences in mammographic density measures. Methods We established an international consortium (DENSNP) of 19 studies from 10 countries, compr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
3
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 31 publications
7
77
3
13
Order By: Relevance
“…The relation between genetic variants and MD has been studied by different groups finding significant associations with several inter and intragenic SNPs. [5][6][7][8][9][10] In relation with the pooled cross-sectional analysis 11 of common breast cancer susceptibility variants and MD, the SNP rs10483813 in gene RAD51L1 was not assessed in our study, while the association between the rs3817198 variant in gene LSP1 with MD was not statistically significant (p 5 0.2676) although the OR was in the same direction (OR (per minor allele increase and likelihood high vs. low density) 5 1.16; CI 5 0.89-1.51) (see Supporting Information File 7). Finally, the two previous genome-wide association studies (GWAS) 12,13 have identified new genetic variants associated with MD, one in gene ZNF365 (rs10995190) and another between genes TBX5 and TBX3 (rs1265507).…”
Section: Epidemiologymentioning
confidence: 99%
“…The relation between genetic variants and MD has been studied by different groups finding significant associations with several inter and intragenic SNPs. [5][6][7][8][9][10] In relation with the pooled cross-sectional analysis 11 of common breast cancer susceptibility variants and MD, the SNP rs10483813 in gene RAD51L1 was not assessed in our study, while the association between the rs3817198 variant in gene LSP1 with MD was not statistically significant (p 5 0.2676) although the OR was in the same direction (OR (per minor allele increase and likelihood high vs. low density) 5 1.16; CI 5 0.89-1.51) (see Supporting Information File 7). Finally, the two previous genome-wide association studies (GWAS) 12,13 have identified new genetic variants associated with MD, one in gene ZNF365 (rs10995190) and another between genes TBX5 and TBX3 (rs1265507).…”
Section: Epidemiologymentioning
confidence: 99%
“…An international consortium, DENSNP, pooled together 19 studies (16,895 Caucasian women) with data on established breast cancer susceptibility variants and quantitative mammographic density measures [19]. The initial publication pooled cross-sectional analyses of common breast cancer susceptibility variants in 14 independent loci and mammographic density measures.…”
Section: Breast Cancer Risk Loci In Relation To Mammographic Densitymentioning
confidence: 99%
“…Desmoplastic tissues were radiographically detected as areas denser than the fat and designated mammographic densities (3)(4)(5). High mammographic density is one of the strongest risk factors for breast cancer development and is associated with common breast cancer susceptibility variants ( 6 ).…”
mentioning
confidence: 99%